Phosphorus deficiency promotes root:shoot ratio and carbon accumulation via modulating sucrose utilization in maize - Xiao, Zu-Dong; Chen, Zhen-Yuan; Lin, Yi-Hsuan; Liang, Xiao-Gui; Wang, Xin; Huang, Shou-Bing; Munz, Sebastian; Graeff-Hönninger, Simone; Shen, Si; Zhou, Shun-Li (Journal of plant physiology, 2024)
Phosphorus deficiency usually promotes root:shoot ratio and sugar accumulation. However, how the allocation and utilization of carbon assimilates are regulated by phosphorus deficiency remains unclear. To understand how phosphorus deficiency affects the allocation and utilization of carbon assimilates, we systematically investigated the fixation and utilization of carbon, along with its diurnal and spatial patterns, in hydroponically grown maize seedlings under low phosphorus treatment. Under low phosphorus, sucrolytic activity was slightly inhibited by 12.0% in the root but dramatically inhibited by 38.8% in the shoot, corresponding to the promoted hexose/sucrose ratio and biomass in the root. Results point to a stable utilization of sucrose in the root facilitating competition for more assimilates, while increasing root:shoot ratio. Moreover, starch and sucrose accumulated in the leaves under low phosphorus. Spatially, starch and sucrose were oppositely distributed, starch mainly in the leaf tip, and sucrose mainly in the leaf base and sheath. Evidence of sucrose getting stuck in leaf base and sheath suggests that carbon accumulation is not attributed to carbon assimilation or export disturbance, but may be due to poor carbon utilization in the sinks. These findings improve the understanding of how low phosphorus regulates carbon allocation between shoot and root for acclimation to stress, and highlight the importance of improving carbon utilization in sinks to deal with phosphorus deficiency.